How Smart Destinations Influence Tourist Satisfaction and Revisit Intention? An Integrated TAM Perspective - Denis Fidita Karya; Mohamad Yusak Anshori (Universitas Airlangga, 2026)
Objective: This study aims to analyze the influence of smart destination and digital information quality on tourist satisfaction and revisit intention through perceived usefulness and perceived ease of use in digitally based tourism destinations. Design/Methods/Approach: This study employed a quantitative research design using purposive sampling. Data were collected from 250 tourists who had utilized digital tourism services, including online ticketing systems, tourism applications, and digital information platforms. The proposed research model was analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. Findings: The results indicate that smart destination and digital information quality positively and significantly influence perceived usefulness and perceived ease of use. Furthermore, perceived usefulness and perceived ease of use significantly enhance tourist satisfaction, while satisfaction positively influences revisit intention. The mediation analysis shows that perceived usefulness and perceived ease of use significantly mediate the relationship between smart destination and satisfaction. In contrast, only perceived ease of use significantly mediates the relationship between digital information quality and satisfaction, whereas the mediating role of perceived usefulness is not supported. These findings suggest that tourists place greater emphasis on the usability of smart tourism technologies and integrated digital experiences than on the functional value of digital information alone in shaping satisfaction. Originality/Value: This study contributes to the smart tourism and Technology Acceptance Model (TAM) literature by demonstrating how smart destination and digital information quality influence tourist satisfaction through different cognitive mechanisms. The findings show that the effects of smart destination are transmitted through both perceived usefulness and perceived ease of use, whereas digital information quality influences satisfaction primarily through perceived ease of use. This evidence provides a more nuanced understanding of technology acceptance in digitally enabled tourism destinations. Practical/Policy Implication: The findings suggest that destination management organizations should prioritize investments in integrated digital infrastructure, user-friendly tourism applications, and seamless digital services to enhance tourist satisfaction and encourage revisit intention. Policymakers are also encouraged to strengthen smart tourism governance and support sustainable digital transformation initiatives to improve destination competitiveness.